An improved plasmid for transformation of Neurospora crassa using the pan-2 gene as a selectable marker - Wilson Low; Gregory Jedd (Fungal Genetics Reports, 2008)
The pOKE103 plasmid can be used to transform Neurospora crassa using the pan-2 gene (NCU10048.3) as a selective marker. We mapped the pan-2 fragment to the right arm of LG VI, contig 4, and found that it carries a pan-2 linked gene, atg-12 (NCU10049.3). We report the removal of atg-12 to produce an improved plasmid, pOKE104.